Performance of Interconnected Hybrid ZigBee-Optic for Extended Wireless Sensor Networks - Octarina Nur Samijayani; Aina Sabrina; Raihan Zaky Thamrin; Dwi Astharini; Ary Syahriar (Journal of ICT Research and Applications, 2024)
Wireless sensor networks (WSNs) are widely used to monitor remote areas far away from the monitoring center. For large-scale or high-capacity WSNs, when they contain many sensor nodes, a transmission system with low latency and large bandwidth is required. In order to extend the network range, the use of optical communication is one of the alternatives to provide more capacity and a longer range. This study discusses the performance of a range-extended WSN utilizing a hybrid of ZigBee and optic transmission. The performance of the proposed method was evaluated by analyzing the throughput, delay per meter, package loss, and error, which were then compared to a ZigBee-Wifi based system. The experimental results showed that the throughput of the hybrid ZigBee-Fiber Optic (ZigBee FO) system was about 12% greater than that of the ZigBee-Wifi system, and it transmitted the sensor data with a significantly lower delay, reduced by 83%, compared to the ZigBee-Wifi. The package loss and error of ZigBee-FO was 35.7% lower than that of ZigBee-Wifi. Based on these results, the ZigBee-FO WSN has the advantage of significantly improving network performance by reducing the transmission delay, therefore it is beneficial in extending the WSN range.